PENDAMPINGAN LATIHAN TARI DOLALAK - Dwipraptono Agus Harjito (Asian Journal of Innovation and Entrepreneurship, 2015)
Before doing staging, exercise routine needs to be done. Dolalak dance trainingassistance program at Children's SDN Tridadi is done so that children are ready and more experts. Exercises accompanied by an expert instructor who is a dancer.